Lineage-related polypeptide markers in acute lymphoblastic leukemia detected by two-dimensional gel electrophoresis. - Hanash, S M (1986)
We have utilized two-dimensional polyacrylamide gel electrophoresis, coupled with ultrasensitive silver staining, to identify lineage-related polypeptide markers in lymphoblasts from children with acute lymphoblastic leukemia. Twelve polypeptides were detected that could distinguish between the major subgroups of acute lymphoblastic leukemia. These included a new marker for common acute lymphoblastic leukemia and markers for cells of B and T lineages. Analysis of the two-dimensional patterns also allowed the tentative identification of T-cell lineage in two cases with an otherwise undifferentiated non-T-cell non-B-cell phenotype. Two-dimensional electrophoresis thus provides a powerful tool for the delineation of the cell of origin in leukemia.